Obesity of Information Covid-19 Children Vaccine and Parents Digital Literacy Ability - Rachmawati, Indri; Pratama Putra, Raditya; ., Yulianti; Nur Aini Noviar, Tri (KnE Social Sciences, 2023)
This study aims to obtain data related to the “tabbayun” attitude of parents in understanding digital literacy in accessing information through social media, especially information on Covid-19 vaccinations for children aged between 06 and 11 years. The purposeless information in our brains can make us lose focus and ultimately make us unable to believe anything. Therefore, it is important to know how tabbayun parents are able to access information, especially the Covid-19 vaccination. Reasoned action theory with quantitative research methods and descriptive approaches chosen for this research, with data collection techniques were carried out through questionnaires, interviews, and supported by documentation, observation, and surveys. This research is expected to be a reference for parents in understanding digital literacy so that they are not trapped in with loads of information, as well as policymakers in conducting socialization and information related to health in the community, especially related to children’s health. To gain an understanding of how parents filter the rapid flow of information so that they are not trapped by inaccurate or even misleading information regarding the Covid-19 vaccination. The results of this study indicate that parents already understand well and are able to filter the information they get. But often, others, including spouses have different understanding patterns, causing debate. And parents also convey vaccination information to children in a language that is easy for children to understand, especially regarding information on Covid-19 vaccination. Impractical information to this literacy ability will be effected to the children vaccination permission and causes parents misunderstanding about the information. Keywords: digital literacy, obesity information, family communication, online media, Covid-19 vaccination